2017
DOI: 10.2298/abs160327101o
|View full text |Cite
|
Sign up to set email alerts
|

Carnosol promotes endothelial differentiation under H2O2-induced oxidative stress

Abstract: Oxidative stress causes deregulation of endothelial cell differentiation. Carnosol is a potent antioxidant and antiinflammatory compound. In the present study, we examined whether the antioxidant effect of carnosol might protect bone marrow stem cells against H 2 O 2 -induced oxidative stress and promote endothelial differentiation. We examined cell viability by the MTT assay; oxidative stress and apoptosis were analyzed through changes in ROS levels, apoptotic ratio and caspase-3 activity; changes in protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In the laboratory setting, carnosol has been proven to exert a cardioprotective effect by increasing the cell viability of H9c2 cardiomyoblast cells in the presence of lipopolysaccharides (LPS) [ 49 ]. This result is consistent with a previous study by Ou et al [ 50 ], which revealed that carnosol improved the viability of rats’ multipotent progenitor cells (MAPCs) induced by hydrogen peroxide (H 2 O 2 ).…”
Section: Role Of Terpenophenolic Compounds On Inflammation and Apopto...supporting
confidence: 93%
“…In the laboratory setting, carnosol has been proven to exert a cardioprotective effect by increasing the cell viability of H9c2 cardiomyoblast cells in the presence of lipopolysaccharides (LPS) [ 49 ]. This result is consistent with a previous study by Ou et al [ 50 ], which revealed that carnosol improved the viability of rats’ multipotent progenitor cells (MAPCs) induced by hydrogen peroxide (H 2 O 2 ).…”
Section: Role Of Terpenophenolic Compounds On Inflammation and Apopto...supporting
confidence: 93%